Evaluación física, química y biológica de la Laguna de Patarcocha - Cerro de Pasco y propuesta de recuperación ecológica - Murga Paulino, Luis Rolando (2011)
In this work of investigation the characteristics have been evaluated physical, chemical and biological of The Lagoon of "Patarcocha", located in the region Pasco, city of Pasco's Hill; who presents a pollution due to the fearlessness of garbage and unloads of effluent; it due to the insensibility of the population who lives about the Lagoon and to the lack of a ring collector of desague. The information in average obtained (for the period 2009-2010), for Patarcocha's Lagoon was: pH 8.27, temperature 11.17°C, metallic elements like the Ace 0.0114 ppm, Cd 0.0114 ppm, Cr 0.0049 ppm, Cu 0.0116 ppm, Faith 0.627 ppm, Mn 1.535 ppm, Pb 0.041 ppm, Zn 0.113 ppm. For the case of total Coliformes 11 x103 NMP/100 ml and fecal Coliformes 4x103 NMP/100 ml. On the basis of the compiled information, one proposed an immediate recovery (Reforestation of Patarcocha's Lagoon, construction of a fence perimétrico of 1376.57m, to avoid the proliferation of dogs and porks to anticipate diseases and to prohibit I effected actions of landfill in Patarcocha's Lagoon), To Medium term (To recover Patarcocha's Lagoon across processes of fitorremediación for wetlands, introducing plants of Watercress, appearing a fall in the development of coliformes of 11 x103 to 4.5 x102 as well as the increase of the O2 disuelto of 4.38 ppm to 8.13 ppm (what indicates an oxygenation of the plant watercress on the waters) and in the long term (to elaborate an Integral Plan with the purpose of preserving and preserving this natural resource, to achieve a supported environment and the development of economic activities as the tourism, which allows the well-being of the settler of the zone).